Yahoo Web Search

  1. Sort by

  1. LHS: 4^(x-1)=(2^2)^(x-1)=2^(2x-2) RHS: 32^4=(2^5)^4=2^20 Therefore 20=2x-2 x=11

    1 Answers · Education & Reference · 24/01/2014

  2. ... -- We cross multiply both LHS and RHS (cos (2x)) ( 1 - tan (x)) = (1+ tan(x)) (1 - sin(2x)) Expanding...

    1 Answers · Education & Reference · 28/01/2014

  3. ... that we are done with the RHS, we have to work on the LHS cos(2A) = cos (A+A) = cos A cos A - sin A...

    1 Answers · Education & Reference · 26/01/2014

  4. LHS = cos² (3x) - cos² (x) => [ ( cos 3x + cos x ) * ( cos 3x - cos x...

    1 Answers · Education & Reference · 21/01/2014

  5. LHS: 2 csc 2u = 2 / (sin 2u) = 2 / (2 sin u cos u) = 1 / (sin u cos u) = (1/sin u) * (1/cos u) = sec u csc u = RHS

    1 Answers · Education & Reference · 26/01/2014

  6. ...1 -1 | -4 ) we can now apply row operations to obtain identity matrix on LHS r2 → r1 - r2 (1 1 | -6 ) (0 2 | -2) r2 → 0.5r2 (1 1 | -6 ) (0 1 | -1...

    1 Answers · Education & Reference · 22/01/2014

  7. First make x on LHS and other variable y on RHS thus we get, X = -2 -6Y Now...

    1 Answers · Education & Reference · 25/01/2014

  8. there could be 2 possibilities on LHS here since you didn't include exponential parenthesis...take the 4th root of the RHS If LHS is 1st possibility, you use newton's method...

    2 Answers · Education & Reference · 20/01/2014

  9. (sinx) (tanx) / 1- cosx = secx + 1 LHS = sin x * ( sin x / cos x ) divided by ( 1 - cos x ) => sin²...

    1 Answers · Education & Reference · 05/12/2013

  10. ... = 8i^2 - 10ij + 3j^2 + [-4i - 2ij + 2j +j^2] = 8i^2 - 12ij + 4j^2 - 4i + 2j LHS = RHS Hence proved!!

    1 Answers · Education & Reference · 25/11/2013

  1. Try asking your question on Yahoo Answers